Almost a lottery: the influence of team strength on success in penalty shootouts. (2nd September 2020) - Wunderlich, Fabian; Berge, Felix; Memmert, Daniel; Rein, Robert
ABSTRACT: Three aspects of penalty shootouts that have not been examined in the literature so far are 1) the influence of overall team strength on penalty success, 2) the viability of a forecasting model for penalty shootouts, and 3) the existence of a penalty-specific home advantage. To this end, a sample consisting of 1067 penalty shootouts from 14 cup competitions was investigated. Team strength was estimated based on betting odds and results show that stronger teams win significantly more shootouts compared to weaker teams. A forecasting model, based on an out-of-sample approach, suggests that the effect of team strength on success is rather small as the winning probability remains around 40% even for very weak teams against very strong teams. Thus, for weaker teams it seems advantageous to focus on drawing a game against stronger teams as their probability of success is much greater during a penalty shootout compared to normal game play. In contrast to the robust evidence of a home advantage during normal game play the results further indicate an absence for a home (or away) advantage during penalty shootouts. The results presented are therefore highly valuable for coaches in supporting clear tactical recommendations.